Individual Monitoring of Behavior to Enhance Productivity and Welfare of Animals in Small-Scale Intensive Cattle Grazing Systems - Anzai, Hiroki; Hirata, Masahiko (Frontiers in Sustainable Food Systems, 2021)
To enhance productivity and welfare of individual animals maintained as a group, management based on individual behavioral tendencies is essential, which requires individual monitoring of animal behavior. Several behavior monitoring systems are currently available to livestock producers. The data obtained from these systems are analyzed to detect significantly high or low frequencies or intensities of behavior associated with estrus, calving and poor health conditions based on thresholds or past trends of the monitored individual. However, because behavior under grazing is more complex and changeable than under confinement, behavioral symptoms are more difficult to detect, and on-farm monitoring of individual animal behavior has been less validated and utilized in grazing systems. Nevertheless, individual monitoring of all animals in a herd is more feasible and cost-effective in small-scale intensive grazing systems because these systems pursue high productivity at the individual level with smaller herd size than large-scale extensive systems. Individually tailored management to enhance productivity and welfare will be possible by focusing on inter-individual differences in behavior within a herd. Behavior of an individual can be analyzed and understood in more detail by comparing it with those of the herd mates. Higher or lower levels of specific activities than the other animals can be associated with health disorders, temporal changes in physiological states, or productivity- or welfare-related traits. More sensitive monitoring and detection of behavioral responses of individuals to changes in nutritional, physical and social environments will lead to more efficient and welfare-conscious management that better meets the needs of individuals.